A masked initiation region in retinoblastoma protein regulates its proteasomal degradation - Takuya Tomita (Nature Portfolio, 2020)
Human papilloma virus (HPV) E7 protein destabilizes the retinoblastoma protein (Rb) by inducing its ubiquitination in cervical cancer cells, however proteasomal degradation requires cleavage of Rb after Lys 810 and so far it has been unclear how Rb cleavage contributes to its degradation. Here, the authors combine cell based and in vitro assays and show that calpain cleavage exposes a region in Rb that is recognized by the proteasome, leading to rapid proteolysis of Rb, whereas the proteasome cannot initiate degradation efficiently on full-length Rb.